Operative Treatment of Complications After Fractures of Calcaneus - Doi, Toshiro; Tono, Osamu; Oga, Masayoshi; Nakano, Soichiro; Seo, Kenichi; Tamaru, Takuya; Hatanaka, Toshiyuki; Ikuta, Kou; Arima, Jyunichi (Orthopedics & Traumatology, 2001)
The Westhues' method or closed reduction (Omotos' method) appears to be an effective treatment for calcaneal fracture. Some patients, however, complain of persistent pain. We report 4 cases (5 feet) showing surgical complications of calcaneal fractures. These complaints are related to the occupation of the patient, especially patients who were carpenters and streetplejack often complained of persistent pain at the talo-calcano joint or the external malleolar region. Such cases require not only accurate reduction of the talo-calcano joint, but also correction of the prominent buldging of the lateral calcaneal cortex. CT, Peroneal synovigram, and block were effective for diagnosis.